ACL Reconstruction in the Multiple Ligament Injured Knee - Marx, Robert G.; Wolfe, Isabel A. (The Journal of Knee Surgery, 2020)
Multiple ligament knee injuries are complex and can result from sports injuries or high energy trauma. The proper diagnosis and treatment of multiple ligament knee injuries are essential, and careful evaluation and planning are required to achieve successful outcomes. Anterior cruciate ligament (ACL) reconstruction in the multiple ligament injured knee is complicated by several factors, necessitating additional technical considerations. Patient selection, surgical timing, graft selection, and surgical technique require consideration specific to the ACL component of these injuries. We present a summary of the current knowledge with respect to the treatment of ACL injuries in the context of the multiple ligament injured knee.
Keywords: anterior cruciate ligament reconstruction; knee dislocation; posterior cruciate ligament; medial collateral ligament